CO2 and CH4 emissions in relation to nutrient cycling and decomposition in a neotropical peatland, Panama - Wright, Emma Louise (2011)
Tropical peatlands play an important role in the global carbon cycle, but little is known about the factors which regulate carbon dioxide (CO2) and methane (CH4) fluxes from these ecosystems. To improve our understanding of the potential impact of future changes in climate and/or land-use, this study aimed to quantify current fluxes of these gases from a large domed peatland, San San Pond Sak, in Panama and assess the influence of environmental factors. Three sites with differing dominant vegetation species (Raphia taedigera, Campnosperma panamensis and Cyperus species) and nutrient status were investigated between February 2007 – September 2009 using a combination of in situ closed chamber gas sampling and ex situ headspace gas sampling to quantify current and potential gas fluxes from the peat surface and at depths of 2 m from the surface. Physical and chemical properties of the peat were determined concurrently. Laboratory experiments were carried out to investigate patterns of litter decomposition and microbial activity. Gas fluxes differed significantly between sites. CO2 fluxes were greatest at the C. panamensis site (100–400 mg m-2 h-1), followed by the R. taedigera (74–352 mg m-2 h-1) and Cyperus sp. (59–294 mg m-2 h-1). The seasonal patterns associated with rainfall were similar for all sites, with the release of CO2 being greatest during the dry season. CH4 fluxes also varied between sites, but no seasonal variation was evident. CO2 flux varied diurnally at the C. panamensis and Cyperus sp. sites, perhaps due a circadian rhythm in vegetation processes. CO2 and CH4 production occurred throughout the upper 2 m of the profile, both in situ and ex situ, with potential CO2 fluxes of up to 1,000 mg m-2 h-1 being found in the surface layer. The peat became increasingly recalcitrant and P-limited with increasing depth. Measurements of litter decomposition and microbial activity indicated that the availability of labile substrates and nutrients differed between sites. In conclusion, CO2 and CH4 fluxes differed between sites experiencing similar environmental conditions, and were influenced by variation in environmental factors. Fluxes varied on both short- and long- timescales, but not at all sites. The magnitude of the gas fluxes was influenced by different environmental factors at each site, indicating that fluxes and the most important driving variables vary dependent on surface vegetation even within a single peatland system. With regard to climate and/or land-use change, it was concluded that San San Pond Sak peatland would be sensitive to water table drawdown, with the likely outcome of increased CO2 releases and the potential for CH4 uptake, rather than release.